Identity, Nationalism and Threats to Northeast Asia Peace. Issue 3 (2nd September 2018) - Shibata, Ria
Abstract: The escalating public debate over amendment of the Japanese constitution centres on the war-renouncing principles of Article 9 — the symbol of Japan's pacifist identity. Since elected to power, Prime Minister Shinzo Abe and his supporters have been steadfastly pushing to revise the constitution to remove pacifist constraints on the nation's Self-Defense Forces. In the face of growing insecurities generated by long economic stagnation, regional threats posed by North Korean missiles and rising Chinese hegemony, Japanese conservative politicians feel it is time to overhaul Japan's humiliating postwar regime represented by the pacifist constitution and restore Japan's pride and independence. This article examines the resurgence of nationalist discourse in Japan as a response to Japan's threatened identity and esteem. As the Japanese people become increasingly exposed to nationalist narratives and realistic threats, how have these affected their desire to maintain a pacifist identity? This paper further examines the pacifist attitudes of today's Japanese youth and to what extent they are in favour of changing the constitution to adopt a stronger military defence.